Diskursus Puasa Weton Jawa dalam Perspektif ‘Urf - Baedhowi, Baedhowi; Miftachul Ihsan , Azim; Sumarjoko, Sumarjoko (El-Qenon: Journal of Islamic Law, 2024)
In the Javanese community, there are various traditions, ranging from cultural and artistic forms to religious activities. One of the traditional practices still carried out by the Javanese is the Weton fasting. This tradition is performed by the Javanese people every 35 days, in accordance with the Javanese market days (Pon, Wage, Kliwon, Legi, Pahing). This research aims to understand what the Weton fasting tradition is and how it is viewed in terms of ’urf (customary practice). This qualitative research uses field studies, descriptive analysis, and Islamic law to observe and directly understand the lives of those who still practice it. Data collection techniques are based on primary data obtained from interviews with the community, elders, and religious leaders in Kandangan who still observe this tradition. Secondary data is obtained from books, journals, documents, and other sources, which are then analyzed using descriptive techniques. The results of the research show that the Weton fasting tradition is practiced by the Javanese community because it has many benefits, including health, as an expression of gratitude to God, as a means of self-restraint from desires, and so on. Additionally, from an Islamic perspective, this practice is permissible even though there is no specific religious text discussing it, because this practice falls into the category of ’urf shahih, which means it is a practice that does not contradict religious or governmental regulations